A sealed-bid auction that matches the English auction - Motty Perry; Elmar Wolfstetter; Shmuel Zamir (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
This paper analyzes a two-stage sealed-bid auction that is frequently employed in privatization, takeover, and merger and acquisition contests. This auction format yields the same expected revenue as the open ascending (English) auction, yet is less susceptible to preemptive bidding and collusion.
urn:nbn:de:kobv:11-10060032
Keywords: D44; 330; Auctions